The colorblind screen : television in post-racial America - Nilsen, Sarah; Turner, Sarah E. (New York University Press, 2014)
"In The Colorblind Screen, the contributors examine television's role as the major discursive medium in the articulation and contestation of racialized identities in the United States. While the dominant mode of televisual racialization has shifted to a "colorblind" ideology that foregrounds racial differences in order to celebrate multicultural assimilation, the volume investigates how this practice denies the significant social, economic, and political realities and inequalities that continue to define race relations today. Focusing on such iconic figures as President Obama, LeBron James, and Oprah Winfrey, many chapters examine the ways in which race is read by television audiences and fans. Other essays focus on how visual constructions of race in dramas like 24, Sleeper Cell, and The Wanted continue to conflate Arab and Muslim identities in post-9/11 television. The volume offers an important intervention in the study of the televisual representation of race, engaging with multiple aspects of the mythologies developing around notions of a "post-racial" America and the duplicitous discursive rationale offered by the ideology of colorblindness."--Publisher's website